2001
DOI: 10.1097/00007890-200110150-00012
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bone Loss and Fracture After Lung Transplantation

Abstract: Antiresorptive therapy with a bisphosphonate decreases the fracture rate and preserves bone mass 1 year after lung transplantation. In end-stage lung disease patients with osteopenia or osteoporosis, bisphosphonate therapy should be initiated before transplant surgery is contemplated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 17 publications
1
34
1
Order By: Relevance
“…Approximately half of the patients were treated with bisphosphonate therapy in both groups, which did not differ between both groups. In a pilot study, aggressive antiresorptive therapy preserved or increased BMD prior to and following transplantation by administration of a bisphosphonate prior to and following transplantation, resulting in only 4% of symptomatic fractures, compared to our current study fracture rate of 8% [9]. The status of antiresorptive therapy prior to transplantation in our study is not known.…”
Section: Discussioncontrasting
confidence: 51%
“…Approximately half of the patients were treated with bisphosphonate therapy in both groups, which did not differ between both groups. In a pilot study, aggressive antiresorptive therapy preserved or increased BMD prior to and following transplantation by administration of a bisphosphonate prior to and following transplantation, resulting in only 4% of symptomatic fractures, compared to our current study fracture rate of 8% [9]. The status of antiresorptive therapy prior to transplantation in our study is not known.…”
Section: Discussioncontrasting
confidence: 51%
“…Similarly, in a prospective, uncontrolled pilot study using intravenous pamidronate in lung transplant recipients, the fracture rate decreased and bone mass preserved at 1-year posttransplantation 52. In a study of renal transplant recipients, repeated doses of intravenous pamidronate preserved vertebral BMD during treatment and 6 months after cessation of treatment 53…”
Section: Specific Types Of Osteoporosismentioning
confidence: 97%
“…Many of these studies have been small and most have not been randomized or controlled (7). Beneficial effects of pamidronate on indirect parameters, such as bone mineral density (BMD), have been shown in patients undergoing heart, liver, lung and kidney transplantation (8)(9)(10)(11)(12). One investigator suggested that aledronate is efficacious in preventing the natural course of bone loss associated with LT (13).…”
Section: Introductionmentioning
confidence: 99%